Combating the "Forces of Darkness": The Cult of Blessed Rupert Mayer, 1945-1987 - Lemmons, Russel (Fides et historia, 2018)
The article examines the cult that arose around the German Jesuit Priest Rupert Mayer and the process by which he was beatified by Pope John Paul II in the late Cold War period. Topics discussed include Mayer's role in the Catholic resistance against National Socialism and the spiritual struggle against totalitarianism, and his influence upon Christians confronting challenges to their religious liberty.